Seagrass-Associated Biodiversity Influences Organic Carbon in a Temperate Meadow - Richard Unsworth (Oceans, 2024)
There is increasing interest in the role that seagrasses play in storing carbon in the context of climate mitigation, but many knowledge gaps in the factors controlling this storage exist. Here, we provide a small case study that examines the role of infaunal biodiversity in influencing seagrass and the carbon stored in its sediments. A total of 25 species of invertebrate were recorded in an intertidal Zostera marina meadow, where these species were dominated by polychaete worms with no bivalves present. We find organic carbon storage (within the top 20 cm) measured by AFDW to be highly variable within a small area of seagrass meadow ranging from 2961 gC.m−2 to 11,620 gC.m−2 with an average (±sd) of 64602 ± 3274 gC.m−2. Our analysis indicates that infaunal communities are significantly and negatively correlated with this sediment organic carbon. However, this effect is not as influential as hypothesised, and the relatively small sample size of the present study limits its ability to provide strong causality. Other factors, such as algal abundance, curiously had a potentially stronger influence on the carbon in the upper sediments. The increasing richness of infauna is likely reducing the build-up of organic carbon, reducing its ecosystem service role. We believe this to likely be the result of bioturbation by specific species such as Arenicola marina and Ampharete acutifrons. A change in sediment organic carbon suggests that these species could be key drivers of bioturbator-initiated redox-driven organic matter turnovers, influencing the microbial processes and remobilizing sediment compounds. Bioturbators should be considered as a limitation to Corg storage when managing seagrass Corg stocks; however, bioturbation is a natural process that can be moderated when an ecosystem is less influenced by anthropogenic change. The present study only provides small-scale correlative evidence with a range of surprising results; confirming these results within temperate seagrasses requires examining this process at large spatial scales or with targeted experiments.